Electrical and mechanical performance difference on piezoelectric segmentation in a passive MEMS DC current sensor applicable to two-wire DC appliances. (18th November 2016) - Yang, Xu; Fu, Yupeng; Wang, Dong F
Abstract: As society develops in intelligence, DC is being widely used in all kinds of field in modern life, which means that a sensitive and convenient DC sensor is necessary to monitor it. Compared with other kinds of current sensor, the proposed passive MEMS DC current sensor has several significant features: power-free passive sensing, small size and low cost. In this work, the performance difference of a cantilever-based bending MEMS DC current sensor among three segmentation PZT plates was first experimentally discovered. The distribution difference of X -dir ( X -direction) stress along the Y axis is confirmed through FEM analysis. An optimized structure with two slots at the root of the cantilever has been proposed to minimize the difference of average X -dir stress on an area attached to three PZT plates. A nearly linear relationship between the output voltage V output and the AC current has been obtained through both theoretical calculation and experimental verification. The sensitivity of the developed MEMS DC current sensor is 40–25 mV A −1 in the current range of 0–400 mA. It is found that there is a good consistency among the calculation, experiment and simulation results.